2005
DOI: 10.1177/107110070502600710
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Forefoot Pressure Changes After Second Metatarsal Neck Osteotomy

Abstract: Overall, our results indicated that the Weil metatarsal neck osteotomy is effective at offloading the second metatarsal head at neutral and heel rise positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Several studies measuring pressures associated with DP osteotomy showed a similar trend . In a clinical study, Vandeputte et al showed similar pressure reductions post‐op (88.3 kPa/5.9 mm shortening = 15.0 kPa/mm) to the slopes of the second metatarsal PP and second metatarsal shortening regressions in our study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several studies measuring pressures associated with DP osteotomy showed a similar trend . In a clinical study, Vandeputte et al showed similar pressure reductions post‐op (88.3 kPa/5.9 mm shortening = 15.0 kPa/mm) to the slopes of the second metatarsal PP and second metatarsal shortening regressions in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In a clinical study, Vandeputte et al showed similar pressure reductions post‐op (88.3 kPa/5.9 mm shortening = 15.0 kPa/mm) to the slopes of the second metatarsal PP and second metatarsal shortening regressions in our study. In a statically loaded cadaveric study, Khalafi et al reported a significant decrease in pressure under the operated second metatarsal of 36% (70.6–45.1 kPa) in neutral position and 65% (813–281.4 kPa) in 45° of plantar flexion and an increase in pressure under the first metatarsal in neutral position. Significant decreases in pressure also occurred under the third metatarsal, contrary to our study, possibly explained by axially loading the specimens and not simulating the entire gait cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence in this study all patients had more than 1 lesser metatarsal osteotomy. 2,16 In the case of isolated long second metatarsal and callosity, a Weil osteotomy with fixation is a favorable procedure as this enables perfect control of the planned proximal migration of the metatarsal head. 13,16,18,30 When using minimally invasive surgery in the forefoot, there is concern about iatrogenic neurovascular and tendon damage.…”
Section: Discussionmentioning
confidence: 99%
“…2,16 In the case of isolated long second metatarsal and callosity, a Weil osteotomy with fixation is a favorable procedure as this enables perfect control of the planned proximal migration of the metatarsal head. 13,16,18,30 When using minimally invasive surgery in the forefoot, there is concern about iatrogenic neurovascular and tendon damage. However with appropriate training and 3-dimensional anatomic awareness of the foot, the risk of neurovascular and tendon injury associated with minimally invasive techniques in the forefoot is minimal.…”
Section: Discussionmentioning
confidence: 99%